Targeted nanoliposomes for precision rheumatoid arthritis therapy: a review on mechanisms and in vivo potential - Rushikesh Girase; Nayan A. Gujarathi; Amey Sukhia; Sri Sai Nikitha Kota; Tulshidas S. Patil; Abhijeet A. Aher; Yogeeta O. Agrawal; Shreesh Ojha; Charu Sharma; Sameer N. Goyal (Drug Delivery)
Rheumatoid arthritis (RA) is an inflammatory immune-triggered disease that causes synovitis, cartilage degradation, and joint injury. In nanotechnology, conventional liposomes were extensively investigated for RA. However, they frequently undergo rapid clearance, reducing circulation time and therapeutic efficacy. Additionally, their stability in the bloodstream is often compromised, resulting in premature drug release. The current review explores the potential of targeted liposomal-based nanosystems in the treatment of RA. It highlights the pathophysiology of RA, explores selective targeting sites, and elucidates diverse mechanisms of novel liposomal types and their applications. Furthermore, the targeting strategies of pH-sensitive, flexible, surface-modified, PEGylated, acoustic, ROS-mediated, and biofunctionalized liposomes are addressed. Targeted nanoliposomes showed potential in precisely delivering drugs to CD44, SR-A, FR-β, FLS, and toll-like receptors through the high affinity of ligands. In vitro studies interpreted stable release profiles and improved stability. Ex vivo studies on skin demonstrated that ultradeformable and glycerol-conjugated liposomes enhanced drug penetrability. In vivo experiments for liposomal types in the arthritis rat model depicted remarkable efficacy in reducing joint swelling, pro-inflammatory cytokines, and synovial hyperplasia. In conclusion, these targeted liposomes represented a significant leap forward in drug delivery, offering effective therapeutic options for RA. In the future, integrating these advanced liposomes with artificial intelligence, immunotherapy, and precision medicine holds great promise.